Cognitive Structure of College Students and Teaching Strategies of Ideological and Political Education Under Educational Psychology - Zhao, Jing (Frontiers in Psychology, 2022)
The ideological and political education (IPE) situation is constantly developing and changing. In modern globalization, the ideological education of college students has received great attention. The purpose is to strengthen morality and cultivate people as the basic point of a college education. The principles of educational psychology are adopted to integrate IPE into the whole process of college teaching and help students develop healthily for a long time. First, IPE psychology's concept and subject attribute under educational psychology are expounded. Next, the concept and development of cognitive structure theory are introduced. Moreover, educational constructivist measures are analyzed. Furthermore, the cognitive structure of college students' self-cognition and IPE is interpreted and analyzed using cognitive psychology. Then, a questionnaire is designed to study the influencing factors of political education strategies in colleges. Finally, the questionnaire is collected to summarize the influencing factors and put forward optimization strategies. The results show that using the principles of educational psychology and cognitive psychology to investigate can accurately understand modern college students' self-cognitive structure and ideological and political cognitive structure. The opportunity factor greatly impacts the IPE strategy of college students. More than 97% think that it has an impact, of which more than 51% think that it has a great impact and more than 21% think that it is the decisive factor. Challenge factors greatly impact college students' IPE strategies. More than 97% think they have an impact, of which more than 55% think they have a great impact, and more than 24% think they are decisive factors. It shows that educational psychology is conducive to the progress of political education in colleges and the improvement of college students' ideological and political levels. This exploration provides a new direction for educational psychology research in ideological and political work.